The Sultan Mahmud Badaruddin II Museum as an Educational Tourism Site and a Local Historical Resource in South Sumatra - Tomy Wijaya; Fatimah Alauwiyah; Hudaidah Hudaidah; Muhammad Reza Pahlevi; Alif Bahtiar Pamulaan (MASI Mandiri Edukasi, 2026)
This research is motivated by the underutilization of the Sultan Mahmud Badaruddin II Museum as an educational tourism site and a resource for local historical education, despite its substantial collections on the Palembang Darussalam Sultanate, colonialism, and South Sumatran culture. This study aims to clarify the use of the museum as an educational tour, analyze its role as a repository of local historical knowledge, and identify challenges and opportunities for its improvement within the context of history education in schools. The study employed a descriptive qualitative methodology, using data collection techniques including observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman framework. The findings reveal that the SMB II Museum has implemented educational tours through guided tours, cultural workshops, and thematic exhibitions that provide contextual learning experiences for students. Nonetheless, the museum's usage has been subpar due to insufficient facilities, a lack of innovative collection display, limited engagement from schools, and poor communication between the museum and educational institutions. These findings highlight the imperative of modernizing educational media, improving collaboration between museums and schools, and securing local government support to ensure the museum functions effectively as a center for local history education.